Perancangan Sistem Informasi Pendaftaran Siswa Baru di MTsN 6 Agam Menggunakan Bahasa Pemrograman PHP/MYSQL - Humala, Indra; Musril, Hari Antoni; Supriadi, Supriadi; Okra, Riri (Institut Teknologi Pendidikan Indonesia, 2023)
The background of this research is that schools still carry out the administrative registrationprocess manually which requires a lot of paper, there are quite a number of prospective newstudent applicants, so there are many errors in recording prospective student data. This causes the registration process to be less effective and efficient, so it is necessary to have a new student registration information system at MTsN 6 Agam. The method used in this research is the Research and Development (R&D) Research Method, which is a method used to produce a product, the system development model uses the System Development Life Cycle (SDLC) using the waterfall model which consists of Communication, ‎Planning, Modeling, Construction, and Deployment. Product testing uses the ISO/IEC 25010 standard, which consists of Functional usability, Compatibility, and Usability testing. Language testing and black box testing are also carried out Based on the results of the research that the author did, the author was able to create a new student registration information system product at MTsN 6 Agam using the PHP programming language and MySQL database. The results of the functional suitability test obtained a score of 100% very feasible, compatibility 100% very feasible, usability score 91.52% very feasible, language testing results 95% very feasible, andblack box testing results 100%.